Women survivors of female genital mutilation/cutting: A collaborative process of engaging them as ambassadors of change in Hargeisa, Somaliland - Ahlberg, Beth Maina; Ahmed Elmi, Shadia; Gaas, Abdirahman Osman; Johansson, Annica; Mahmoud Warsame, Amina (Somali Health Action Journal, 2022)
The overall question guiding this research was why after so many years of research and other forms of interventions to eradicate female genital mutilation, it persists. This article is about a special group of women who undergo medical surgery to repair the damage they had endured after genital mutilation/cutting (FGM) in childhood. The process describes how women are encouraged to reflect on their experiences before and after medical surgery and to engage in dialogue on how FGM can be stopped. The study builds on participatory action research aiming to generate knowledge while simultaneously attempting to change the system, or in this case, the attitudes to and reasoning around FGM. However, due to the outbreak of COVID-19, the entire process that should have lasted for at least three years, could not be implemented. This paper therefore covers only the initial process of reaching the affected women, whom we call ambassadors of change, and the organization of the first dialogue workshop. The process started with pre-dialogue mapping that involved visiting women who had received care through an NGO and interviewing them individually or in small groups about their FGM complications and their life after medical surgery. They were also invited to a dialogue workshop with other women and representatives from the government and civil society, to talk about FGM, their pains and how to stop FGM. A total of 34 women participated in the workshop where they discussed their experiences and exchanged views on how to end the practice. The use of participatory action research is discussed and the study indicates the need for using innovative methods to mobilize and engage community members and policy makers to end FGM.